Attitudes Toward Seeking Professional Psychological Help Among Health-Related and Non-Health-Related Students: A Cross-Sectional Study - Nasser Ahmed Alkhamias; Salim Abdulraouf Almane; Mohammed Abdulaziz Albahli; Saud Mossab Alholiby AlbinZaid; Abdullah Duhailan Alduhailan; Abdullah Almaqhawi (Healthcare, 2026)
Background: Mental health disorders are an increasing concern in Saudi Arabia, including in the Eastern Province, where one study found that of the 42.5% of medical students who reported a clear need for mental health services, only 16.2% had actually used them. Stigma and other psychosocial factors are thought to shape help-seeking behavior, yet comparative studies remain scarce. This study compares attitudes toward seeking professional psychological help, and perceived stigma, between students in health-related and non-health-related programmes at King Faisal University. Methods: In this cross-sectional study, 589 students at King Faisal University, Saudi Arabia, were recruited through convenience sampling. Data were collected with an online, self-administered questionnaire covering sociodemographic characteristics and three validated Arabic instruments: the Attitudes Toward Seeking Professional Psychological Help–Short Form (ATSPPH-SF), the Stigma Scale for Receiving Psychological Help (SSRPH), and the Hopkins Symptom Checklist-25 (HSCL-25). Results: Of the 589 respondents, 580 (98.5%) were included in the analysis—279 (48.1%) health-related and 301 (51.9%) non-health-related students. Most were aged 18–21 (76.9%), Saudi nationals (96.9%), single (91.9%), and of middle income (79.2%). Attitudes toward seeking professional psychological help did not differ significantly between health-related and non-health-related students (Welch’s t(566) = −1.48, p = 0.138, Cohen’s d = −0.12, a negligible effect). Perceived stigma (SSRPH) was significantly higher among health-related students (10.85 vs. 10.16; t(578) = 2.56, p = 0.011). Perceived social stigma was inversely and significantly associated with attitudes toward seeking professional psychological help (r = −0.262, p < 0.001). Together, stigma and psychological distress (HSCL-25) explained a modest 7.9% of the variance in help-seeking attitudes (R2 = 0.079). Conclusions: Health-related and non-health-related students at this single university did not differ significantly in their attitudes toward seeking professional psychological help. Perceived stigma showed the stronger association with less favorable attitudes, whereas psychological distress was associated with a smaller, positive association. These findings, from a single-center convenience sample, point to a need for stigma-reduction efforts and confidential mental health services at King Faisal University.